Values for peak ground acceleration and peak ground velocity using in seismic hazard assessment for Song Tranh 2 hydropower region - Thanh, Tran Thi My; Minh, Nguyen Le; Vung, Vi Van; Irikura, Kojiro (Vietnam Journal of Earth Sciences, 2014)
Song Tranh 2 Hydropower Plant was built in 2010 with the seismic design for maximum possible magnitude M= 5.5. On March 2011 the people of Bac Tra My area nearby the Song Tranh 2 dam began to feel slight ground motion accompanying with the sound of explosions. This phenomenon happened with increasing frequency. On November 15, 2012, an earthquake of magnitude M = 4.7 occurred. This earthquake caused some damage to Song Tranh project management office and houses in the Bac Tra My area. An unusual series of frequent earthquakes has alarmed, caused significant worries and stress for both the local people and local authorities. Results of our survey of the area around Song Tranh 2 (December 2012) have shown that recently, the earthquakes occur frequently and caused minor damage on some houses. While the houses had cracks in the walls, but the columns did not experience any damage. The damage is consistent with the shaking of the intensity in the range of VI - VII (MSK scale). However, the maximum value of acceleration (PGA) measured from accelerometer recordings is equivalent to a higher shaking intensity levels of VII - VIII. Value of the maximum velocity (PGV) measured from accelerometer recordings is more in line with the survey results which is equivalent to the shaking intensity levels VI - VII. The reason for this difference is that PGV is less affected by shaking than PGA at high frequencies. The key conclusion from this experience is that we should also consider PGV in earthquake hazard assessment for the design works because so far we have only used the PGA.References Avila-Barrientos, L., Valdes-Gonzalez, C., 2011: Generation of isoseismal maps for Mexico using velocity and acceleration data. Nat Hazards, Vol. 59, No. 2, pp 655-664. Cosenza, E., Manfredi, G., 2000: Damage indices and damage measures. Prog. Struct. Engg Mater., Vol. 2, pp 50-59. Wald, D.J., , Quitoriano, V., Heaton, T.H.,  Kanamori, H., 1999: Relationships between Peak Ground Acceleration, Peak Ground Velocity, and Modified Mercalli Intensity in California. Earthquake Spectra, Vol. 15, No. 3, pp. 557-564. Department of Seismological Survey, 2003: Earthquake Catalog of Southern Vietnam. Institute of Geophysics (in Vietnamese). Department of Seismological Survey, 2014: Earthquake catalog of Tranh River No.2 hydroelectric Plant area and surrounding, Institute of Geophysics (in Vietnamese). Fujiwara, H., Kawai, S. Aoi, S.,  Morikawa, N.,  Senna, S.,  Kudo, N.,  Ooi, M., Hao, K.X.,  Wakamatsu, K., Ishikawa, Y.,  Okumura, T., Ishii, T.,  Matsushima, S., Hayakawa, Y.,  Toyama, N.,  Narita, A., 2009: Technical reports on national seismic hazard maps for Japan, Technical note of the NIED, Vol.336. Institute of Geophysics, 2003: Estimation of Seismic hazard in Tranh River No.2 hydroelectric Plant area, Institute of Geophysics (in Vietnamese). Jaimes, M.A., Arredondo, C.,  Reinoso, E., Ordaz, M,, 2008: Probabilitics seismic hazards analysis to contents and non-structural elements: correlation between peak ground acceleration and velocity. Earthquake Engineering, 14th World Conference, October 12-17, 2008, Beijing, China. Kermani, E., Jafarian, Y., Baziar, M.H., 2009: New Predictive Models for the Vmax /amax Ratio of Strong Ground Motions using Genetic Programming. International Journal of Civel Engineering, Vol. 7, No. 4, December 2009, pp 236. Le Huy Minh, Le Tu Son, Le Van Dung, Dinh Quoc Van, Nguyen Thanh Tung, Nguyen Huu Tuyen, Tran Tuan Anh, Phan Trong Trinh, Ngo Thi Lu, 2012: Report on earthquake survey in the Tranh River No.2 hydroelectric Plant, North Tra My district, Quang nam province, Institute of Geophysics, September 2012 (in Vietnamese). Le Huy Minh, Nguyen Tien Khiem, Nguyen Van Giang, Nguyen Dinh Kien. Nguyen Dinh Xuyen, Le Tu Son, et al., 2012: Report on earthquake survey in the Tranh River No.2 hydroelectric Plant, North Tra My district, Quang nam province, Institute of Geophysics, April 2012 (in Vietnamese). Le Huy Minh, Tran Tuan Anh, Phan Trong Trinh, Pham Van Hung, Le Tu Son et al., 2011: Report on earthquake survey in the Tranh River No.2 hydroelectric Plant, North Tra My district, Quang nam province, Institute of Geophysics, December 2011 (in Vietnamese). Makris N.,  Black, C.J., 2004: Evaluation of Peak Ground Velocity as a “Good” Intensity Measure for Near-Sourc Ground Motions. Journal of Engineering Mechanics, Vol. 130, No. 9, pp 1032-1044. Medved'ev, S.W., Sponheuer, W., Karnik, V., 1965: Seismic intensity scale version msk 1964, UNESCO/NS/SEISM/28, 7 May 1965, Paris. Miyake, H., Iwata, T., Irikura, K., 2003: Source characterization for broadband ground-motion simulation: Kinematic heterogeneous source model and strong motion generation area. Bull. Seismol. Soc. Am., Vol. 93, No. 6, pp 2531-2545. Sawada, T.,  Hirao, K., Yamamoto, H., Tsujihara, O., 1992: Relation between maximum amplitude ratio (a/v, ad/vz) and spectral parameters of earthquake ground motion. Earthquake Engineering, Tenth World Conference, Vol. 2, pp 617. Wu, Y-M., Shin, T-Ch., Chang, Ch-H., 2001.Near Real-Time Mapping of Peak Ground Acceleration and Peak Ground Velocity Following a Strong Earthquake. BSSA, Vol. 91, No. 5, pp 1218 - 1228. Wu, Y-M., Teng, T-L., Shin, T-Ch., Hsiao, N-Ch., 2003: Relationship between Peak Ground Acceleration, Peak Ground Velocity and Intensity in Taiwan, BSSA, Vol. 93, No. 1, pp 386-396. Zhu, T., Tso, W., Heidebrecht, A., 1988: Effect of Peak Ground a/v Ratio on Structural Damage. J. Struct. Eng., Vol. 114, No. 5, pp 1019-1037.